(untitled) (World Bulletin of Public Health, 2026)
This article comprehensively analyzes the biophysical structure of blood, its components, and its main physicochemical properties. The composition of blood, consisting of plasma and formed elements, as well as important indicators such as viscosity, density, osmotic pressure, and oncotic pressure, are scientifically described. In addition, the rheological properties of blood, namely its behavior as a non-Newtonian fluid, the deformability of erythrocytes, and its role in microcirculation, are examined. The transport, protective, regulatory, and thermoregulatory functions of blood are also analyzed from a physical perspective. The results of the study demonstrate the important role of blood biophysical parameters in maintaining physiological balance, early disease detection, and modern clinical diagnostics